Investigating the additive interaction of QT-prolonging drugs in older people using claims data - Meid, Andreas; Medem, Anna von; Seidling, Hanna; Quinzler, Renate; Haefeli, Walter E. (Drug safety, 2017)
IntroductionDrugs that potentially prolong the QT interval carry the risk of life-threatening Torsades de pointes (TdP) ventricular arrhythmia.ObjectiveThe objective of this study was to investigate the potential additive risk for ventricular arrhythmia with concomitant prescriptions of QT-prolonging drugs.MethodsClaims data for persons aged ≥65 years between 2010 and 2012 in Germany were analyzed and all cases hospitalized for ventricular arrhythmia were selected. In a case-crossover analysis, exposure with QT-prolonging drugs according to the Arizona Center for Education and Research on Therapeutics (AZCERT) classification of ‘known,’ ‘conditional,’ and ‘possible’ TdP risk was determined in respective event and control windows preceding hospitalization. Conditional logistic regression was applied to derive odds ratios (ORs).ResultsAmong 6,849,622 health-insured persons, we identified 2572 patients newly hospitalized for ventricular arrhythmia. Drugs with ‘known’ risk were more frequently prescribed in the event window than in the control window (309 vs. 239; P < 0.001). The number of drugs with an attributed ‘known’ risk of TdP was significantly associated with hospitalization for ventricular arrhythmia (OR: 2.22; 95% confidence interval [1.51-3.25]; P < 0.001), while increased risk estimates were also obtained upon categorization into one and two or more drugs compared with no drugs for the combined group of drug with ‘known’ (1.52 [1.16-2.00]) and ‘conditional’ risk (2.20 [1.42-3.41]). Pairwise comparisons and trend tests based on these classification categories could not demonstrate a significantly increased risk of two or more drugs compared with one drug.ConclusionBeyond suitable single-drug classifications for QT-associated risk estimation, the situation when there is co-prescription of several drugs appears to be complex and may not be extrapolated to all possible multi-drug combinations.
First online: 29 November 2016
Gesehen am 24.09.2018